Whey Protein Versus Whey Protein Hydrolyzate for the Protection of Azoxymethane and Dextran Sodium Sulfate Induced Colonic Tumors in Rats - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (SPRINGER, 2012)
Recent studies have shown that whey protein has many useful effects including its anti-cancer effect. In this study we have compared the protective effect of dietary whey protein with whey protein hydrolyzate against azoxymethane and dextran sodium sulfate induced colon cancer in rats. We used a rat model of the colon cancer induced by administration of azoxymethane followed by repeated dextran sodium sulfate ingestion which causes multiple tumor development. Colon tissues were analyzed histologically in addition to biochemical analyses performed by measuring lipid peroxidation, protein oxidation and glutathione levels in both of colon and liver tissues of rats after sacrification. Macroscopic and microscopic tumors were identified in all groups that received azoxymethane followed by repeated dextran sodium sulfate. Group fed with whey protein hydrolyzate showed significantly less macroscopic and microscopic tumor development compared with group fed with whey protein. The protocol applied to generate an appropriate model of colon cancer was successful. Whey protein hydrolyzate was found to be more effective in preventing colon tumor development compared with whey protein.
Keywords: Colon cancer; Azoxymethane; Dextran sodium sulfate; Whey protein; Whey protein hydrolyzate; PLASMA GLUTATHIONE LEVELS; ANTIOXIDANT ACTIVITY; MICE; SUPPLEMENTATION; CARCINOGENESIS; EXPRESSION; COLITIS; CANCER; SOY